Linguistic Diversity in Self-Access Learning Spaces in Japan: A Growing Role for Languages Other than English? - Katherine Thornton (Studies in Self-Access Learning Journal)
In line with foreign language instruction in general, foreign language provision in self-access learning centres (SALCs) has been dominated by English language learning. This is largely due to the nature of the internationalisation agenda in Japan, termed kokusaika, which emphasises English as the most important international language, the learning of which can facilitate Japanese economic advancement (Hashimoto, 2017; Kubota & Takeda, 2021). Largely missing from this narrative is a promotion of multiculturalism within Japan between different migrant populations, for many of whom English is as much a foreign language as it is for Japanese nationals (Tsuneyoshi, 2018). In order to truly internationalise, Japan must understand and embrace the linguistic and cultural diversity within its borders. Therefore, international education should focus on more than simply English education. This is as true for self-access facilities as it is for the mainstream curriculum. While there is some provision in some facilities for languages other than English (LOTE), as yet, no systematic investigation into the degree and nature of this provision has been conducted. Using data from a survey administered with coordinators of SALCs across Japan, this study investigated the degree to which SALCs in Japan are focusing on LOTE and the different ways in which they support these languages. The results revealed increasing focus on LOTE in some SALCs, in terms of materials and services offered, and significant linguistic diversity among SALC staff. However, common heritage and indigenous languages in Japan are largely absent, and a tendency to see language provision primarily as the appropriate balance between English and Japanese still persists in some SALCs.